Prognosis value of circulating telomere repeat binding factor 2 and leukocyte telomere length in breast cancer mortality - Sasmita, Dhyas MA.; Anwar, Sumadi L.; Heriyanto, Didik S.; Paramita, Dewi K.; Hendrawan, Fandi; Aryandono, Teguh (Narra Sains Indonesia, 2025)
Telomere repeat binding factor 2 (TRF2) is currently a novel tumor marker, yet its clinical implication has not been investigated. The aim of this study was to investigate the prognostic value of circulating TRF2 and leukocyte telomere length in 5-year mortality in breast cancer patients. In this cohort retrospective study, breast cancer patients were included and the length of telomeres and circulating TRF2 were quantified. Receiver operating characteristics and the Youden index were used to determine the optimal cut-off. To analyze the overall survival rate in 5 years, Kaplan Meier analysis was used, while the prognostic value of both variables was analyzed in Cox proportional hazard regression on both univariate and multivariate models. Our data indicated that the optimal cut-off points for TRF2 and leukocyte telomere length were 598 pg/mL and 0.93 kb, respectively. Based on the optimal cut-off points, the participant’s data was grouped, and our data indicated that the high TRF2 group had a poorer overall survival rate in comparison to the low group (91.3% vs 83.87%; log-rank test; p<0.01). The overall survival between short and long telomeres was comparable (88.24% vs 88.37%; log-rank test; p=0.64). TRF2 (hazard ratio (HR): 3.66; 95%CI: 1.45–9.29) and molecular subtype (p=0.04) were identified as independent factors to predict mortality. In conclusion, a high circulating TRF2 in breast cancer participants was associated with lower overall 5-year survival rates in comparison with the low TRF2 group. Moreover, high TRF2 could predict the mortality of the breast cancer population to be 3.66 times higher than the lower group. In contrast, telomere length was not associated with overall survival rate nor predicting mortality in five years.